Effects of Co-occurring marijuana use and anxiety on brain structure and functioning: A systematic review of adolescent studies. (June 2018) - Cancilliere, Mary Kathryn; Yusufov, Miryam; Weyandt, Lisa
Abstract: The prevalence of marijuana use among adolescents with anxiety disorders in the USA is markedly high and well documented; however, the literature on this co-occurrence's effect on adolescent brain development and functioning is limited. This systematic review searched six databases to 1) explore the literature concerning marijuana use among adolescents with anxiety and 2) examine the effects of marijuana on brain structure and functioning. Overall, 27 studies from six countries were included in this review. Out of these studies, several disparate designs were utilized. The majority of studies revealed an association between marijuana use and anxiety, but the strength of the association and the variability among the studies' designs limited the comparison and warrants additional investigation. Only five studies met criteria that used brain-imaging techniques, and findings were non-conclusive. Future evaluations should further investigate the effects of co-occurring marijuana use and anxiety disorders on brain structure and functioning among adolescents.